PEMERIKSAAN BAKTERIOLOGI ES BATU BALOK DI KOTA KLATEN - agustina, Anita; Al'Azzah, Zuhdiyyah Habibullah (Universitas Muhammadiyah Klaten, 2018)
Ice cubes beams is that cooled water then molded into beams large extremely known to the public and is considered safe to eat. Storage of ice cubes beams that only in put it on the roadside with closed using plastic or sacks and plastic sheeting allow the presence of bacterial contamination. The purpose of this research is analyzing and knows the value of the ALT and MPN Coliform on ice cubes beams that sold in the city of Klaten. The research is observational. A sample of ice cubes beam used is 3 samples to be taken from the seller in in Klaten north, in Klaten central and southern district Klaten. Samples of ice cubes beam were tested ALT and MPN Coliform to determine the value of bacterial contamination. The result of the research using ALT method, shows 2 samples to meet the standard of contamination of samples A and B, while for sample C exceeds the standard of contamination determined by BPOM RI No. HK.00.06.1.52.4011 that is 1x104 UK / ml. For the results of the research using MPN Coliform method, showed that the three samples exceeded the standard of the contamination that has been determined by BPOM RI No. HK.00.06.1.52.4011 ie <3 cells/ ml. The conclusion of this research is that all three samples ice cubes beams unfit for consumed.